Combined hysteroscopy and laparoscopy in evaluation of female infertility - Gandotra, Nikita; Rizvi, Syed Masuma; Sharma, Preeti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Infertility has always been one of the most elusive symptom complexes that perplex the best gynecologists and affects about 10-15% of reproductive age couples. Methods: This descriptive study was conducted in the Postgraduate Department of Obstetrics and Gynaecology at Government Medical College, Jammu for a period of 18 months in which 100 infertile females attending OPD for infertility workup were subjected to detailed relevant history taking followed by physical examination. Diagnostic hysteroscopy and laparoscopy along with laparoscopic chromopertubation was carried out after written informed consent including minimal therapeutic interventions if required. Results: Out of 100 patients included in the study, 67 (67%) presented with primary infertility and 33 (33%) presented with secondary infertility. Combined laparoscopy and hysteroscopy was normal in 13% (13) of cases. Out of 100 patients, abnormal laparoscopic findings were noted in 73% of patients: Endometriosis ( 13%),Polycystic ovaries (12%), Unilateral tubal block (11%), Pelvic inflammatory disease (9%).Abnormal hysteroscopic findings were noted in 47% of patients: Submucous myoma (8%),unilateral ostial block (8%),Endometrial polyp (7%), Hyperplasic endometrium (7%), Cervical stenois (6%).Most common cause of infertility in present study on Combined hysteroscopy and laparoscopy was Endometriosis (13%) followed by Polycystic ovaries (12%),Uterine myoma (12%) out of which 5% myomas were diagnosed on laparoscopy and 8% on hysteroscopy and 1% had myoma diagnosed on both hysteroscopy and laparoscopy. In the primary infertility group most, common finding was Polycystic ovaries (16.4%) followed by Endometriosis (14.9%) and uterine myoma (14.9%) while in patients suffering from secondary infertility, most patients had Bilateral tubal block (18.2%), Pelvic inflammatory disease (12.1%), Unilateral tubal block (12.1%), intrauterine adhesions (12.1%). Conclusions: Combined Hysteroscopy and Laparoscopy is a quintessential tool that provides cost-effective, comprehensive and single set-up diagnostic aid in infertile patients.